Economic Empowerment of Islamic Boarding School Based on Ecoprotection - Lestari Daswan; Samsinar; Siti Nur Annisa Aulia; Indra Nola (Genius: Jurnal Ekonomi Dan Manajemen, 2025)
The purpose of this study was to determine and understand the economic empowerment based on ecoprotection and the implementation of the ecoprotection economic system at the Tahfidz Baitul Qur'an Al Askar Kendari Islamic Boarding School. This study uses a qualitative descriptive method using data collection techniques through interview methods, observation and documentation. Data analysis techniques use data reduction, data presentation and drawing conclusions collected by the author for the purpose of solving a problem or to answer research questions. The findings of this investigation show that the Tahfidz Baitul Quran Al Askar Kendari Pesantren has empowered the pesantren economy by creating several business units according to the needs of the students by implementing three types of economic empowerment patterns applied by the pesantren, namely economic efforts centered on kyai, economic efforts of the pesantren to strengthen operational costs and economic efforts for students. The implementation of the ecoprotection economic system in the business unit of the Tahfidz Baitul Quran AL Askar Kendari Pesantren by not allowing external institutions or communities outside the Pesantren to carry out economic activities in order to provide students with both religious instruction and entrepreneurship skills or knowledge, all business units inside the Pesantren are exclusively owned by the school and run by the students themselves. The Pesantren community's welfare and its own economy can both benefit from the installation of this ecoprotection system